2022
DOI: 10.1002/hyp.14580
|View full text |Cite
|
Sign up to set email alerts
|

Integrating partitioned evapotranspiration data into hydrologic models: Vegetation parameterization and uncertainty quantification of simulated plant water use

Abstract: Accurate simulation of plant water use across agricultural ecosystems is essential for various applications, including precision agriculture, quantifying groundwater recharge, and optimizing irrigation rates. Previous approaches to integrating plant water use data into hydrologic models have relied on evapotranspiration (ET) observations. Recently, the flux variance similarity approach has been developed to partition ET to transpiration (T) and evaporation, providing an opportunity to use T data to parameteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…Evapotranspiration (ET) plays a pivotal role in regulating both surface water and groundwater recharge, holding critical significance for water resources (Ren et al, 2021; Yang et al, 2020). Ecological disturbances, such as those induced by bark beetle activity, can change the hydrological partitioning between evaporation ( E ) and transpiration ( T ) (Schreiner‐McGraw et al, 2022). Previous analysis of hydrological impacts related to bark beetle‐induced forest mortality have suggested that bark beetle infestation can reduce ET and lead to an increase in streamflow (Frank et al, 2014; Vystavna et al, 2018; Wehner & Stednick, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Evapotranspiration (ET) plays a pivotal role in regulating both surface water and groundwater recharge, holding critical significance for water resources (Ren et al, 2021; Yang et al, 2020). Ecological disturbances, such as those induced by bark beetle activity, can change the hydrological partitioning between evaporation ( E ) and transpiration ( T ) (Schreiner‐McGraw et al, 2022). Previous analysis of hydrological impacts related to bark beetle‐induced forest mortality have suggested that bark beetle infestation can reduce ET and lead to an increase in streamflow (Frank et al, 2014; Vystavna et al, 2018; Wehner & Stednick, 2017).…”
Section: Discussionmentioning
confidence: 99%